Penguatan Kompetensi Komunikasi dan Administrasi Karang Taruna melalui Pelatihan Bahasa Indonesia Praktis - Muhammad Ridho Prihatin; Riki Nasrullah; Yermia Nugroho Agung Wibowo; Abdul Aziz Khoiri; Ericha Pranatasya (Yayasan Daarul Huda Kruengmane, 2026)
This community service program aimed to strengthen the communication and administrative competencies of the board members and active members of Karang Taruna Banjarsari, Banyuwangi Regency, through practical Indonesian language training. The program employed a participatory and educational approach based on organizational needs and organizational artifacts. The implementation stages included needs assessment, preparation of training materials, interactive training sessions, editing practice, mentoring in drafting official letters, proposals, and activity reports, reflective evaluation, and the formulation of follow-up actions. The data for this article were derived from the program proposal, training materials, sample practice documents, mentoring records, and the instructional materials produced during the program. Data were analyzed using a descriptive qualitative approach by examining language-related issues, structural completeness, information accuracy, formatting consistency, and document functionality. The findings indicate that the training model successfully integrated language conventions with the practical needs of organizational work. Language rules, which had previously been perceived merely as spelling conventions, were reframed within the broader context of conveying intentions, preparing plans, documenting decisions, and reporting organizational activities. Case-based exercises enabled participants to identify wordiness, unclear objectives, inappropriate target audiences, ambiguous information regarding time and venue, unrealistic budgeting, and incomplete document structures. The program produced practical organizational resources, including training materials on official correspondence, proposal and report templates, examples of sentence revision, and an administrative checklist.